A Nation Like All Others: A Brief History of American Foreign Relations - Warren I. Cohen (Columbia University Press, 2018)
Belief in the United States as a force for good in the world runs deep. Yet an honest consideration reveals a history marred by great crimes and ordinary errors, alongside many achievements and triumphs. In this comprehensive account of American foreign relations from the nation’s founding through the present day, the diplomatic historian Warren I. Cohen calls attention to the uses—and abuses—of U.S. international leadership and the noble as well as the exploitative ends that American power has wrought.